Combination of Triple Therapy and Chronic PPI Use May Decrease Risk of Colonic Adenomatous Polyps in Helicobacter pylori Infection. (12th May 2015) - Zuniga, Rina; Bautista, Josef; Sapra, Katherine; Westerfield, Keith; Williams, Susan; Sy, Alexander M.
Abstract : Aim . The aim of the paper is to determine association between H. pylori and colonic adenomatous polyps and to explore whether treatment or chronic PPI use can mitigate this risk. Methods . This case-control study included 943 patients who had H. pylori testing and underwent colonoscopy. Presence of polyps was the outcome of interest, whereas age, sex, race, H. pylori infection, triple therapy, and chronic PPI use were independent variables. Multivariate regression analysis was used to calculate odds ratios at 95% confidence intervals. This study was approved by the New York Medical College Institutional Review Board. Results . H. pylori was associated with increased odds of colonic adenomatous polyps (adjusted OR 1.43, 95% CI 1.04–1.77), with stronger association among patients older than 50 (OR 1.65, 95% CI 1.18–2.33). Triple therapy (OR 0.69, 95% CI 0.44–1.07) or chronic PPI use (OR 0.69, 95% CI 0.43–1.09) decreased odds of polyp formation. Analysis revealed a statistically significant reduction in patients who received both triple therapy and chronic PPI, lowering the odds by 60% (adjusted OR 0.43, 95% CI 0.27–0.67). Conclusion . There is increased risk of colonic adenomatous polyps among H. pylori -infected patients. Triple therapy or chronic PPI use may mitigate this risk, with further reduction when these two interventions are combined.